ISSUES OF DEVELOPMENT OF ENVIRONMENTAL KNOWLEDGE AND THINKING IN THE DISCOURSE OF SUSTAINABLE DEVELOPMENT GOALS - Khurramov Isroil Abdurashidovich (Western European Studies, 2023)
In this article, the issues of Sustainable Development Goals, the development of environmental knowledge and thinking aimed at improving the way of life and improving the well-being of all mankind are widely covered. Feedback on the process of reflection of objective being in the mind about nature, its components, the laws between them is presented in the Prevention of environmental problems of educators
Keywords: Prevention; educators; nature